Can the German Electricity Market Benefit from the EU Enlargement? Results of Scenario Calculations Using the EMELIE Model - Manfred Horn; Claudia Kemfert; Vitaly Kalashnikov (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
This paper investigates the impacts of the eastern enlargement of the European Union in 2004 and the liberalisation of European electricity markets on Germanys electricity exchange with neighbouring countries and on electricity prices. Thus, electricity imports from Czech Republic have increased sharply in the last few years and have dampened German wholesale prices for electricity. In this paper the EMELIE simulation model, a game theoretic model for the European electricity market, is applied to analyse possible long-term effects of these changes. In the model calculations it is assumed that competition will prevail on the European electricity market in 2030, as far as possible with the existing transmission capacities. Primary energy prices are assumed to increase moderately from 2004 to 2030 (30 % for gas and 15 % for hard coal), and the price for CO2-certificats is assumed to remain high (?25/t). It is further assumed that Germany sticks to the aim to shut down nuclear power stations. In the reference case (no increase of transport capacities, without CO2 costs) model results show a clear increase in Germany?s electricity imports from France and the Czech Republic. With rising CO2 prices imports from France increase slightly, as do Germany?s electricity exports to Poland. In the open-market case (transport capacities are increased and nuclear power stations are built in neighbouring eastern European countries), electricity imports from these countries increase if high energy und CO2-prices prevail. Wholesale prices for electricity in Germany are – according to the model results – higher than in the neighbouring countries with the exception of Austria and the Netherlands. Until 2030, the position of electricity consumers in Germany compared with those in all its neighbouring countries would improve; only in France and Sweden would these wholesale electricity prices be lower than in Germany.
Keywords: 330